2016
DOI: 10.1016/j.carbon.2015.10.066
|View full text |Cite
|
Sign up to set email alerts
|

Structure of graphite precipitates in cast iron

Abstract: This study presents microstructural investigations of graphite precipitates found in cast irons. Binary Fe eC, FeeCeSb and FeeCeCe alloys containing different graphite morphologies (flake and spheroidal) were produced and compared to commercial irons in an attempt to rationalize the effect of Sb and Ce on graphite growth. The extensive use of transmission electron microscopy (mainly electron diffraction and high resolution lattice fringe imaging) enabled further understanding of graphite growth mechanisms. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 34 publications
5
41
1
Order By: Relevance
“…Considering the model shown in Fig. 2-c and recent TEM observations [2,15] suggest to extend to spheroids the 2-D nucleation and growth model developed by Amini and Abbaschian [12] for plate-like growth of graphite from the liquid. Such an approach has been in fact already suggested based on a simple model [16] and is presented here in a much more formal and quantitative way.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Considering the model shown in Fig. 2-c and recent TEM observations [2,15] suggest to extend to spheroids the 2-D nucleation and growth model developed by Amini and Abbaschian [12] for plate-like growth of graphite from the liquid. Such an approach has been in fact already suggested based on a simple model [16] and is presented here in a much more formal and quantitative way.…”
Section: Introductionmentioning
confidence: 78%
“…1. The change in orientation of the c axis at the boundary between two sectors may amount from 10 to several tens of degrees, while the orientation changes within sectors are more limited [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exotic or interesting graphite precipitates could thus be obtained, such as exploded nodules illustrated in Figure 5 which were observed in a Fe-C-Ce alloy. 25 In these precipitates, the sectors of the graphite nodule appear well formed but separated from one another. This goes in line with Ce adsorbing on the prismatic planes along the graphite/liquid interface and slowing down the growth along the prismatic direction.…”
Section: Graphite Growthmentioning
confidence: 96%
“…After doping a Fe-C melt with Sb, it was found that graphite lamellas became wavy and transmission electron microscopy (TEM) observation showed this to be associated with a marked shortening of the SBUs without noticeable change of their thickness. [23][24][25] Other forms of graphite in cast irons may be seen to be similarly made of stacking of SBUs. This was long ago postulated for spheroidal graphite by Mitsche et al 26 and demonstrated with transmission electron microscopy (TEM) by Miao et al 27 The schematic of compacted graphite proposed by Den Xijun et al 28 and the scanning electron microscopy (SEM) observations by Geier et al 29 may be similarly understood.…”
Section: Graphite Growthmentioning
confidence: 99%